E-waste management in collection centres at Kuantan, Pahang - Muhammad Zaki, Mujib (2019)
This research was conducted to study e-waste management in collection centre at Kuantan, Pahang because there is no e-waste recovery facility available in this region. The study only focus on collection centre that authorized under Department of Environment (DOE) which assigned as authorized collector for e-waste in Kuantan, Pahang. This study consists of three main objectives that need to be achieved after completion of this study. Firstly, the objective of this study is to determine the amount of e-waste collected by the collection centre in Kuantan through request from the collection centre’s management. The data requested from the centre only available for two years of operation which is in years 2017 and 2018. Besides, the study also conducted to identify the level of health risks awareness among the e-waste workers at the collection centres through comparison of questionnaire analysis method of worker’s knowledge, attitude and practice (KAP) with the score grading from the previous study and it shows that the workers have a good level of awareness towards health risks. In addition, the study also aims to determine the compliance of the e-waste management with e-waste regulation especially with Environmental Quality Act 1974. To achieve this goal, interview session based on the checklist items has been done with the collection centre’s management and it shows that there is no violation of regulation has been done by the collection centre ever since they start operating the business. However, there are several recommendations for future study based on the research findings, which are ensuring more respondents involved in survey as well as focusing on more collection centres rather than only one centre. In conclusion, this study has come out with an outcome which is all three main objectives of this research were achieved after completion of this study.